The use of monoethanolamine oleate (ethamolin®) in the treatment of lingual hemangioma (Research, Society and Development, 2021)
A 35-year-old male patient attended the Oral and Maxillofacial Surgery and Traumatology outpatient clinic at Hospital da Face in Recife / PE, with a complaint of tongue injury.  On intra-oral clinical examination, a lesion in the lingual apex was observed and, during anamnesis, the patient reported the presence of the lesion since childhood, however, he noticed an increase in the last two years.  The vascular origin of the lesion was confirmed, suggesting a diagnosis of hemangioma.  The treatment instituted was the intralesional injection of Monoethanolamine Oleate (Ethamolin®), a sclerosing agent that has hemostatic properties and its mechanism is based on tissue necrosis.  The aim of this study was to demonstrate sclerotherapy using Ethamolin®, which proved to be a viable, safe and effective therapeutic option in the resolution of the reported vascular neoplasia.  The patient was followed up for three months and showed complete remission of the lesion without recurrences.